Peripherally Inserted Central Catheters as Potential Risk Factors for Failure in Pedicled Latissimus Dorsi Flaps - Efanov, Johnny Ionut (Plast Reconstr Surg Glob Open, 2019)
Pedicled latissimus dorsi musculocutaneous flaps are reliable options for reconstruction of torso and head and neck defects. After ensuring that no kink or external compression occurs on the pedicle, the survival rate exceeds 99%. However, we experienced a complete necrosis of the flap after insertion of a peripherally inserted central catheter line. Intraoperative findings demonstrated thrombosis of the subclavian vein over a large segment, which was found to be the cause of flap failure. The clinical significance of this case report is aimed at raising awareness against insertion of peripherally inserted central catheter lines on the ipsilateral arm of a pedicled latissimus dorsi flap.